Prevention and Punishment of Crimes Against Humanity: The United Nations General Assembly Long-Walk Journey - Ana Paula Lavalle Arroyo; Amadou Jaiteh (Washington University Global Studies Law Review, 2025)
This article traces the efforts within the United Nations to negotiate a convention on the prevention and punishment of crimes against humanity. The authors offer a behind-the-scenes account of the negotiations that led to the decision to convene the United Nations Conference of Plenipotentiaries on the Prevention and Punishment of Crimes against Humanity, the challenges posed by the impasse within the Sixth Committee due to consensus-based diplomacy, and the pivotal roles of civil society and academic experts. The article concludes with an invitation for States to deliver a strong and inclusive treaty that fills a critical gap in international law and ensures accountability for the gravest crimes of concern to humanity.
Keywords: Crimes Against Humanity; United Nations; Sixth Committee; Progress; Civil Society; Accountability